The Influence of Interest and Grit on Indonesian Primary Students’ English Language Performance - Detriana Abuk; Yumna Habibah Nurhasanah; Maria Cilia Nahak; Yeni Novelina Manek (JEES: Journal of Education and Educational Sciences, 2026)
This study investigated the relationship between learning interest, grit, and English language performance among Indonesian primary school students. A total of 240 students from three public elementary schools SDN Negeri 1 Tuk, SDN Negeri 1 Kedung Jaya, and SDN Negeri 1 Kedung Dawa participated in the study. Data were collected using structured questionnaires and analyzed through descriptive statistics, validity and reliability testing, and multiple linear regression analysis. The findings revealed that both interest and grit had significant positive correlations with English performance (r = 0.622, p < 0.001 for interest; r = 0.693, p < 0.001 for grit). Furthermore, regression analysis indicated that grit was the stronger predictor of English achievement (β = 0.503, p < 0.001), compared to learning interest (β = 0.278, p < 0.001), with the model accounting for 52.1% of the variance in performance (R² = 0.521). These results emphasize that while student interest enhances motivation, grit defined as perseverance and sustained effort-is a more influential factor in predicting academic success in English. The study highlights the importance of cultivating both interest and resilience in young learners. Teachers are encouraged to implement strategies that promote long-term motivation and persistence to support better outcomes in English language learning.